Learning with multimedia technology – a promise or reality? - Vernadakis Νικόλαος; Avgerinos Ανδρέας; Zetou Ελένη; Giannousi Μαρία; Kioumourtzoglou Ευθύµης (Inquiries in Physical Education and Sport, 2006)
The purpose of this review was the investigation and critical appraisal of the educational opportunities that the use of Multimedia Instruction promises in the educational environment and especially to the Physical Education. In particular, the paper starts with a detailed description of the advantage and disadvantage of Multimedia Instruction. Continues with a research result report dealing on the learning effects of Multimedia Instruction and a model proposed for developing educational multimedia applications. Finally, a wide range of concerns and problems are identified and considered most of which seem to be related with the ways in which this kind of software is being actually introduced and used within the classroom setting. The studies reviewed fulfilled the following criteria: i) used a quantitative assessment of learning with multimedia technology, ii) included participants from preschool through undergraduate school, iii) used a comparison or control group, iv) conducted internationally and in Greece, and v) published in English or Greek language. Based therefore, on the evidence of this research review it appears that the Multimedia Instruction can be an effective, interesting and attractive way of teaching that supplements the conventional educational process.